The influence of acute and 23 days of intermittent hypoxic exposures on the exercise-induced forehead sweating response - Kacin, A.; Golja, P.; Eiken, O.; Tipton, M. J.; Mekjavic, I. B. (European Journal of Applied Physiology, 2007)
The effect of acute and 23 days of intermittent exposures to normobaric hypoxia on the forehead sweating response during steady-state exercise was investigated. Eight endurance athletes slept in a normobaric hypoxic room for a minimum of 8 h per day at a simulated altitude equivalent to 2,700 m for 23 days (sleep high-train low regimen). Peak oxygen uptake and peak work rate (WRpeak) were determined under normoxic (20.9%O2) and hypoxic (13.5%O2) conditions prior to (pre-IHE), and immediately after (post-IHE) the intermittent hypoxic exposures (IHE). Also, each subject performed three 30-min cycle-ergometry bouts: (1) normoxic exercise at 50% WRpeak attained in normoxia (control trial; CT); (2) hypoxic exercise at 50% WRpeak attained in hypoxia (hypoxic relative trial; HRT) and (3) hypoxic exercise at the same absolute work rate as in CT (hypoxic absolute trial; HAT). Exposure to hypoxia induced a 33 and 37% decrease (P < 0.001) in pre-IHE and post-IHE, respectively. Despite similar relative oxygen uptake during HAT pre-IHE and post-IHE, the ratings of perceived whole-body exertion decreased substantially (P < 0.05) post-IHE. Pre-IHE the sweat secretion on the forehead was greater (P < 0.01) in the HAT (2.60 (0.80) mg cm-2 min-1) compared to the other two trials (CT = 1.87 (1.09) mg cm-2 min-1; HRT = 1.57 (0.82) mg cm-2 min-1) despite a similar exercise-induced elevation in body temperatures, resulting in an augmented (P < 0.01) gain of the sweating response. 'The augmented and during the HAT were no longer evident post-IHE. Thus, it appears that exercise sweating on the forehead is potentiated by acute exposure to hypoxia, an effect which can be abolished by 23 days of intermittent hypoxic exposures.